Bacterial Influence on Alkenones in Live Microalgae - Segev, Einat (J Phycol, 2016)
The microalga Emiliania huxleyi produces alkenone lipids which are important proxies for estimating past sea surface temperatures. Field calibrations of this proxy are robust but highly variable results are obtained in culture. Here we present results suggesting that algal-bacterial interactions may be responsible for some of this variability. Co-cultures of E. huxleyi and the bacterium Phaeobacter inhibens resulted in a 2.5-fold decrease in algal alkenone-containing lipid bodies. In addition levels of unsaturated alkenones increase in co-cultures. These changes result in an increase in the reconstructed growth temperature of up to 2°C relative to axenic algal cultures.